Predicting stock market trend from twitter feed and building a framework for Bangladesh - Karim, Shabab; Abdullah, Tahmid; Tayaba, Umme (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.